Propriedades ópticas não-lineares de terceira ordem em materiais bidimensionais - Lucas Lafetá Prates da Fonseca (2017)
$a This dissertation deals with the study of third-order nonlinear optical effects, specifically the behavior of Four Wave Mixing (FWM), in two-dimensional materials; in this case graphene, hexagonal boron nitride (h-BN) and one heterostructure comprised by graphene on top of few layer h-BN. We have studied the behaviour of FWM intensity as a function of pumping laser energy close to the resonance with phonons in the materials. For h-BN, we have observed an increase in the FWM close to the phonon energy. However, for graphene the FWM is decreased at the phonon energy and for the heterostructure the optical response is dominated by the graphene. This unexpected result was explained by analyzing the electronic structure of both materials. Boron nitride is an insulator, therefore all the electronic transitions involved are virtual, and only the phonon transition is real. On the other hand, graphene is a zero gap semiconductor, and all the electronic transitions are real. We show that for the heterostructure, the graphene response is larger because the third order susceptibility in graphene is greater than h-BN. Finally, we have used the Fano model in order to describe our results as being due the interference between transitions with electronic continuum and discrete phonon states in these materials.